Quality monitoring in transition: The challenge of evaluating translational research programs in academic biomedicine - Rushforth, A; de Rijcke, S (Oxford University Press, 2016)
While the efficacy of peer review for allocating institutional funding and benchmarking is often studied, not much is known about issues faced in peer review for organizational learning and advisory purposes. We build on this concern by analyzing the largely formative evaluation by external committees of new large, ‘translational’ research programs in a University Medical Center in the Netherlands. By drawing on insights from studies which report problems associated with evaluating and monitoring large, complex, research programs, we report on the following tensions that emerged in our analysis: (1) the provision of self-evaluation information to committees and (2) the selection of appropriate committee members. Our article provides a timely insight into challenges facing organizational evaluations in public research systems where pushes toward ‘social’ accountability criteria and large cross-disciplinary research structures are intensifying. We end with suggestions about how the procedure might be improved.